Protective effect of gut microbiota restored by fecal microbiota transplantation in a sepsis model in juvenile mice - Han, Young Joo; Kim, SungSu; Shin, Haksup; Kim, Hyun Woo; Park, June Dong (Frontiers in Immunology, 2024)
Introduction Restoring a balanced, healthy gut microbiota through fecal microbiota transplantation (FMT) has the potential to be a treatment option for sepsis, despite the current lack of evidence. This study aimed to investigate the effect of FMT on sepsis in relation to the gut microbiota through a sepsis model in juvenile mice. Methods Three-week-old male mice were divided into three groups: the antibiotic treatment (ABX), ABX-FMT, and control groups. The ABX and ABX-FMT groups received antibiotics for seven days. FMT was performed through oral gavage in the ABX-FMT group over the subsequent seven days. On day 14, all mice underwent cecal ligation and puncture (CLP) to induce abdominal sepsis. Blood cytokine levels and the composition of fecal microbiota were analyzed, and survival was monitored for seven days post-CLP. Results Initially, the fecal microbiota was predominantly composed of the phyla Bacteroidetes and Firmicutes. After antibiotic intake, an extreme predominance of the class Bacilli emerged. FMT successfully restored antibiotic-induced fecal dysbiosis. After CLP, the phylum Bacteroidetes became extremely dominant in the ABX-FMT and control groups. Alpha diversity of the microbiota decreased after antibiotic intake, was restored after FMT, and decreased again following CLP. In the ABX group, the concentrations of interleukin-1β (IL-1β), IL-2, IL-6, IL-10, granulocyte macrophage colony-stimulating factor, tumor necrosis factor-α, and C-X-C motif chemokine ligand 1 increased more rapidly and to a higher degree compared to other groups. The survival rate in the ABX group was significantly lower (20.0%) compared to other groups (85.7%). Conclusion FMT-induced microbiota restoration demonstrated a protective effect against sepsis. This study uniquely validates the effectiveness of FMT in a juvenile mouse sepsis model, offering potential implications for clinical research in critically ill children.